Shades of red: several lines of evidence reveal a pest of sugarcane as new species of Mahanarva (Hemiptera: Auchenorrhyncha: Cercopidae). - Paladini, Andressa; Carvalho, Gervásio Silva; Cabral-de-Mello, Diogo Cavalcanti [UNESP]; Mariguela, Tatiane Casagrande [UNESP]; Domahovski, Alexandre Cruz; Barão, Kim Ribeiro (Cambridge University Press (CUP), 2025)
Many species of spittlebugs (Auchenorrhyncha: Cercopidae) use sugarcane and other grasses as host plants, and when damage is extensive they are considered pests leading tom economic losses. Mahanarva fimbriolata and Mahanarva spectabilis are the most common in sugarcane and can be distinguished mainly by genital morphology. Recently, another morphotype of Mahanarva occurring in sugarcane fields that did not match the morphologies of either of these Mahanarva species mentioned above has been widely collected in Brazil, raising doubts on the identification of Mahanarva species using sugarcane. Accurate specimen identification is critical for sugarcane pest management, because misidentifications can lead to economic losses and inefficient control strategies. Thus, we combined morphology, geometric morphometrics, and molecular techniques to investigate the hypothesis that this morphotype could be considered a new species of Mahanarva. Morphological analyses included examination of male genitalia and tegminal colouration patterns. We also quantified hindwing shapes using geometric morphometrics; and performed a phylogenetic analysis using the mitochondrial COI gene. Morphological evidence distinguished the new morphotype through unique traits in male genitalia. Geometric morphometrics reliably separated species, with over 89% classification accuracy. Molecular analyses confirmed the morphotype as a distinct lineage closely related to M. fimbriolata and M. spectabilis. Thus, we describe M. diakantha sp. n., demonstrating the effectiveness of an integrative approach in resolving taxonomic challenges. Additionally, we provide formal diagnoses for M. fimbriolata and M. spectabilis. This work underscores the importance of precise taxonomy in agroecosystems, supporting sustainable pest management practices.